An Annotated Description of Shallow Water Holothurians (Echinodermata: Holothuroidea) from Cayos Cochinos, Honduras - Hasbún, Carlos Roberto; Lawrence, Andrew J (Revista de Biología Tropical, 2002)
Taxonomic and biological aspects are presented on five species of shallow water holothurians from the Cayos Cochinos Biological Reserve-CCBR located on the northern Honduran shelf, western Caribbean at 16º N, 86º W. This article provides a taxonomic key of the recorded holothurians and morphometric/morphologic descriptions of their corresponding spicules. These five species belong to a single order (Aspidochirotida) and two families: Stichopodidae (Isostichopus badionotus) and Holothuriidae (Holothuria mexicana, H. thomasi, H. arenicola and Actinopyga agassizi). In addition, the commensal pearlfish, Carapus bermudensis is recorded from H. mexicana and A. agassizi.